MANAJEMEN PROGRAM PENATAAN HALAMAN MELALUI BUDIDAYA BUNGA MIANA SMP BINA HARAPAN JATIGEDE SEKOLAH ADIWIYATA 2025 - Cecep Odim (PT. RANESS MEDIA RANCAGE, 2025)
A clean and green school environment plays an essential role in creating a comfortable and effective learning atmosphere. However, achieving such an environment requires the active involvement of all school members and effective program management. This study aims to examine the management of a school yard arrangement program through the cultivation of Bunga Miana in realizing SMP Bina Harapan Jatigede as an Adiwiyata School at the Sumedang Regency Level in 2025. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, documentation, and triangulation. The results show that the school yard arrangement program was planned participatively through stages of evaluation analysis, aspiration gathering, and program planning involving various stakeholders, emphasizing environmental conservation, empowerment of school members, and local potential development. Its implementation was successful through collaborative efforts using the BMSF Katata approach, integrating conservation values into learning and student character building, with active support from the school community, UNPAD, the local community, and government, as part of a sustainable Adiwiyata School initiative. The program was evaluated comprehensively and systematically through regular monitoring, curriculum assessment, and stakeholder involvement. The evaluation results indicated program effectiveness through improved environmental conditions, increased plant growth, timely execution, enhanced student character, and sustainability potential. Therefore, Bunga Miana cultivation proves effective as a sustainable and educational strategy for managing the school environment in support of achieving the Adiwiyata School status. Keywords: Miana Flower; Program Management; School Yard Arrangement; Adiwiyata SchooL